Dynamic molecular monitoring of retina inflammation by in vivo Raman spectroscopy coupled with multivariate analysis. Issue 9 (6th September 2013) - Marro, Monica; Taubes, Alice; Abernathy, Alice; Balint, Stephan; Moreno, Beatriz; Sanchez‐Dalmau, Bernardo; Martínez‐Lapiscina, Elena H.; Amat‐Roldan, Ivan; Petrov, Dmitri; Villoslada, Pablo
Abstract Retinal tissue is damaged during inflammation in Multiple Sclerosis. We assessed molecular changes in inflamed murine retinal cultures by Raman spectroscopy. Partial Least Squares‐Discriminant analysis (PLS‐DA) was able to classify retina cultures as inflamed with high accuracy. Using Multivariate Curve Resolution (MCR) analysis, we deconvolved 6 molecular components suffering dynamic changes along inflammatory process. Those include the increase of immune mediators (Lipoxygenase, iNOS and TNFα), changes in molecules involved in energy production (Cytochrome C, phenylalanine and NADH/NAD+) and decrease of Phosphatidylcholine. Raman spectroscopy combined with multivariate analysis allows monitoring the evolution of retina inflammation. Raman spectroscopy analysis of the Retinal Ganglion Cell layer of the retina. (A) Design of the analysis of the Ganglion cell layer (GCL) and Retinal Nerve Fiber Layer (RNFL) of the retina based in the physical properties of laser light and anatomical structure of retinal layers. (B) Examples of raw Raman spectra from representative retina sample after 10 hours incubation time (black) and LPS treated retina sample after 10 hours incubation time (red) and 12 hours incubation time (blue). (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)